Removal of methylene blue from aqueous solution by dehydrated wheat bran carbon - Ozer, Ahmet; Dursun, Gulbeyi (Elsevier Science Bv, 2007)
Dyes are usually presents in the effluent water of many industries, such as textiles, leather, paper, printing and cosmetics. The effectiveness of dye adsorption from wastewater has made to get alternative different low cost adsorbent to other expensive treatment methods'. The adsorption of methylene blue onto dehydrated wheat bran (DWB) was investigated at temperatures (25-45 degrees C, initial methylene blue (MB) concentrations (100-500 mg L-1) and adsorbent dosage at the given contact time for the removal of dye. The optimum adsorption conditions were found to be as medium pH of 2.5 and at the temperature of 45 degrees C for the varying adsorbent dosage. Equilibrium isotherms were analysed by Freundlich, Langmuir and Redlich-Peterson isotherm equations using correlation coefficients. Adsorption data were well described by the Langmuir model, although they could be modelled by the Freundlich and Redlich-Peterson model as well. The pseudo-first order and pseudo-second order kinetic models were applied to test the experimental data. It was concluded that the pseudo-second order kinetic model provided better correlation of the experimental data rather than the pseudo-first order model. The mass transfer model as intraparticle diffusion was applied to the experimental data to examine the mechanisms of rate controlling step. It was found that at the higher initial MB concentration, intraparticle diffusion is becoming significant controlling step. The thermodynamic constants of the adsorption process were also evaluated by using the Langmuir constants related to the equilibrium of adsorption at temperatures varied in the range 25-55 degrees C. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: methylene blue; adsorption; dehydrated wheat bran (DWB); equilibrium; kinetic; thermodynamic parameters